Gremlin Regulates Tubular Epithelial to Mesenchymal Transition via VEGFR2: Potential Role in Renal Fibrosis - Marquez-Exposito, Laura; Lavoz, Carolina; Rodrigues-Diez, Raul R.; Rayego-Mateos, Sandra; Orejudo, Macarena; Cantero-Navarro, Elena; Ortiz, Alberto; Egido, Jesús; Selgas, Rafael; Mezzano, Sergio; Ruiz-Ortega, Marta (Frontiers in Pharmacology, 2018)
Chronic kidney disease (CKD) is emerging as an important health problem due to the increase number of CKD patients and the absence of an effective curative treatment. Gremlin has been proposed as a novel therapeutic target for renal inflammatory diseases, acting via Vascular Endothelial Growth Factor Receptor-2 (VEGFR2). Although many evidences suggest that Gremlin could regulate renal fibrosis, the receptor involved has not been yet clarified. Gremlin, as other TGF-β superfamily members, regulates tubular epithelial to mesenchymal transition (EMT) and, therefore, could contribute to renal fibrosis. In cultured tubular epithelial cells Gremlin binding to VEGFR2 is linked to proinflammatory responses. Now, we have found out that in these cells VEGFR2 is also involved in the profibrotic actions of Gremlin. VEGFR2 blockade by a pharmacological kinase inhibitor or gene silencing diminished Gremlin-mediated gene upregulation of profibrotic factors and restored changes in EMT-related genes. Moreover, VEGFR2 inhibition blocked EMT phenotypic changes and dampened the rate of wound healing in response to Gremlin. The role of VEGFR2 in experimental fibrosis was evaluated in experimental unilateral ureteral obstruction. VEFGR2 inhibition diminished the upregulation of profibrotic genes and EMT changes, as well as the accumulation of extracellular matrix proteins, such as fibronectin and collagens in the obstructed kidneys. Notch pathway activation participates in renal damage progression by regulating cell growth/proliferation, regeneration and inflammation. In cultured tubular epithelial cells, Notch inhibition markedly downregulated Gremlin-induced EMT changes and wound healing speed. These results show that Gremlin regulates the EMT process via VEGFR2 and Notch pathway activation, suggesting that the Gremlin/VEGFR2 axis could be a potential therapeutic target for CKD.